PROFIL KOMUNITAS LITERASI DI KOTA JAYAPURA - Yonggom, Aplonia; Iwong, Henry Christope (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2021)
The research was conducted in Jayapura city using qualitative approach and conducted for 5 (five) months. Data retrieval using observation techniques, interviews, Focus Group Discussion (FGD) and library studies. The data was analyzed descriptively. The short-term objectives of this study were: 1) Number of Literacy Communities in Jayapura City 2) Profile of each literacy community 3) Overview of the existence of literacy communities. The long-term goal is expected to provide reference contributions for the government and related agencies on the development of literacy, development of literacy and education communities in Jayapura City. Based on the processing of data obtained descriptively it could be said that the literacy movement in Jayapura city had developed quite well in recent years. This could be seen from various literacy activities such as training, competitions, seminars and book surgery. Support was also provided by governments and non-governmental agencies. Including the emergence of many Community Taman Baca Masyarakat (TBM) and literacy communities. There are 4 literacy communities that are considered to exist enough to conduct literacy activities in Jayapuara City, namely Sastra Papua community (Kosapa), Sekolah Menulis Papua community (SMP), Gerakan Papua Mengajar community (GPM) and the Pilamo Aksara Community. The community was profiled on behalf of other literacy communities in Jayapura.Keywords: community; literacy; literacy readÂ